Characteristics of Acute Asthma Patients Based on Visits to The Emergency Unit and Treatment Costs in Jakarta Islamic Hospital Pondok Kopi - Muhammad Fachri; Farabillah Afifah (Muhammadiyah International Public Health and Medicine Proceeding, 2021)
Proper handling of asthmatics can maintain the patient's quality of life. Visits of asthmatic patients to the Emergency Department (ER) indicate uncontrolled asthma and a marker of risk for future asthma exacerbations. Uncontrolled asthma can increase health costs, the risk of hospitalization, and can also cause death. This research at to determine the relationship of acute asthma patients who visit the emergency department with costs of treatment. Analytical descriptive research with cross-sectional study design. The population of this study was acute asthma sufferers who went to the emergency department of RSIJ Pondok Kopi in the period August 1, 2016 – August 1, 2017, and all of the population was used as a sample of 35 people. Data collection is done by studying the documentation of medical record data. The results showed 32.4% of respondents aged 41-49 years, 62.9% were female and had a high school education level (SMA), 40% of respondents were housewives (IRT), 65.7% had acute asthma. moderate, and the most precipitating factor is respiratory tract infection. Most visits to the ER were 30 patients (85.7%) with 1 visit and not accompanied by complications. The results of the highest treatment costs ranged from Rp. 300,000 – Rp. 400,000 as many as 22 patients (62.9%) with guaranteed treatment used were non-BPJS. The costs incurred by each acute asthma patient with 1 visit to the ER are lower than 2 times or more than 2 visits. It was also found that the number of acute asthma patients with complications was greater in costs than those without complications.